Justiça restaurativa, sustentabilidade e bem viver: contribuições ao manejo de conflitos socioambientais na Amazônia brasileira - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This Thesis discusses the use of theoretical-methodological references of restorative justice for the management of socio-environmental conflicts in the Brazilian Amazon, particularly in the state of Pará. The research focuses on experiences built in the west of the state and in the metropolitan region of Belém. It supports the hypothesis that restorative justice can play an important role in the transformation of patterns that contribute to the occurrence of socio-environmental conflicts and harmful acts that affect nature and humanity in the Brazilian Amazon. But to do so, it needs to integrate worldviews that look at the relationship of human beings with the natural world from perspectives that are beyond modern and colonial epistemologies and worldviews. For this reason, the Thesis aims to debate a socio-environmental approach to restorative justice capable of contemplating the notions of sustainability and good living present among indigenous peoples, quilombolas and traditional communities from the Brazilian Amazon. It is an eminently qualitative research in the interdisciplinary field of environmental sciences, with special emphasis on social and human aspects, and which epistemologically adopts a transformative perspective in restorative justice. As one of the stages of the research, a literature review was carried out on restorative justice and socio-environmental conflicts in the Brazilian Amazon, which led to the visualization of the particularities of these conflicts as clashes of perceptions and actions around the relationship between humanity and nature, closely linked to colonization and the expansion of the capital frontier. This review also demonstrated the need to expand the interpretation of restorative justice beyond a conception limited to social conflict resolution technologies, demanding a broader approach that is appropriate to the complexity of handling socio-environmental conflicts in the Amazon region. In order to understand restorative justice in the state of Pará, in turn, an autoethnographic exercise was undertaken, based on the researcher’s personal experiences in the restorative field that began more than a decade ago, which was nourished by her direct participation in the management of restorative justice programs and policies within the Judiciary. Another stage of the research was the study of 03 cases of socio-environmental conflict treated from restorative justice references in the state of Pará. The results achieved were presented in the format of a portfolio of academic productions carried out between 2019 and 2023, preceded by an introduction that summarizes the proposal of the Thesis and followed by a conclusion that summarizes the findings of the research. Among the results, the Technical Note “Strategies for Socio- Environmental Peacebuilding: Restorative Justice” stands out, a theoretical-methodological proposition for the management of socio-environmental conflicts in the Brazilian Amazon, aimed mainly at actors of the justice system who are called upon to act in the face of socio-environmental conflicts involving indigenous peoples, remnants of quilombos and traditional communities, but which it is hoped can also be appropriated by subjects outside the justice system, especially for the individuals and collectives involved. In the conclusions, it is stated that environmental injustices in the Brazilian Amazon are related to the expansion of settler colonialism in the region. The perception of socio-environmental restorative justice is emphasized as a journey that includes the search for truth, justice, mercy and peace and that socio-environmental reconciliation is a possible horizon but presupposes the need to address accountability and reparation for the damage caused and violence practiced.
Keywords: Amazônia; Conflitos socioambientais; Justiça restaurativa; Sustentabilidade; Bem viver; CNPQ:: CIENCIAS AMBIENTAIS; Processos de urbanização da Amazônia e sustentabilidade